Violent authenticity: the politics of objects and images in Ishiguro. Issue 1 (2nd January 2021) - Dean, Dominic
ABSTRACT: Kazuo Ishiguro's work explores acute anxieties towards the human and material objects – from dead bodies to artworks – that circulate in a globalised world and seem to threaten its future. Tracing these objects alongside the images through which Ishiguro's characters attempt to navigate from compromised pasts into complicated futures, this article develops a new reading across Ishiguro's narratives of globalisation, migration, and mass production. Though Ishiguro's work eludes transparent political allegory, there is nevertheless an underlying consistency in the politics of objects and images found there – one that uncannily reflects, and audaciously responds to, a fetish for authenticity that destroys the future even when seeking to secure it. The article looks across Ishiguro's oeuvre, where – from jazz records and sunglasses in Nocturnes (2009), to the cassette tape referenced in Never Let Me Go 's (2005) title – the treatment of second-hand, mass-produced and borrowed objects mirrors the abuse of humans perceived to lack authenticity, for the sake of preserving an image of 'original' – ethnic, national, or even ecological – value. Ishiguro's political significance emerges through his exposing the gaps between object and image, countering violent authenticity with private autonomy, unexpectedly achieved with help from the most banal objects.